“Hope amidst uncertainty”- parents’ experiences during their children stayed in pediatric intensive care unit with respiratory failure: A qualitative phenomenology study - Nisachon Sangsuk; Watcharawan Wongkruasorn; Kanokwan Pethsuwan; Jidapa Poogpan (Jurnal Keperawatan Padjadjaran, 2025)
Background: The hope of parents was vital, especially in the context of children’s high risk of mortality due to respiratory failure. Purpose: To discover how parents hoped with children who had respiratory failure in pediatric intensive care unit of a general hospital located in northeastern, Thailand. Method: This qualitative research method was based on Heideggerian hermeneutic phenomenology. Participants were purposively chosen. A semi-structured interview guide was used to keep focus during the interviews. The 12 participants were recruited by the principle of data saturation. Lifeworld’s approach of van Manen concept used for data analysis. Lincoln and Guba’s criteria were used in approaching trustworthiness.  Results: This study found 8 main themes: Lived body: 1) Blaming my lateness, hopefully recovery. 2) Comforting myself, come to terms with the truth (Tum jai). Lived space: 3) Floating in the dark, death was imminent, hopefully hospital discharge. Lived Time: 4) Waiting was torturous, every second counts. Lived relation: 5) Requiring humanized care. 6) Hoping holy things help my child heal. Lived things: 7) Enduring excruciating pain with life-saving devices. 8) Keeping a phone close at hand but not wanting to hear its call. Conclusion: Parents depended on hope as the way to cope with uncertainty and the possibility of death. Nurses should support parents in coping with guilt, uncertainty, and despair by fostering holistic approaches, humanized care, enhanced communication, effective pain management and promoting family centered care.